Alhindi sebagai Pengobatan Herbal Infeksi Covid-19: Studi Takhrij dan Syarah Hadis - Luqmanul Hakim; Muhamad Yoga Firdaus; Mujiyo (Gunung Djati Conference Series, 2022)
This study aims to discuss the hadith about alhindi as a herbal treatment for Covid-19 infection. The method used in this research is to use a qualitative approach that emphasizes literature study through the takhrij and syarah hadith methods by applying contemporary analysis. The results of this research and discussion show that the hadith about qusthul hindi as herbal medicine has authentic quality according to takhrij reviews so that it can be accepted and practiced as an Islamic proposition. Then the syarah of this hadith shows that qusthul hindi is not the final cure for Covid-19 infection. But it only serves as a recommendation for additional supplements or prevention and early treatment for Covid-19 patients and for patients with comorbidities, or for patients with other diseases. Especially for Covid-19, most of the symptoms include respiratory system disorders, throat problems, pneumonia and fever, more recommendations for treatment using qusthul hindi. The conclusion of this study is that this hadith about qusthul hindi is maqbul for herbal treatment, but it must be subject to proper rules and supervision from medical experts.